2017
DOI: 10.21070/jees.v2i2.964
|View full text |Cite
|
Sign up to set email alerts
|

Interactional Strategies Used by Low Level Learners in Public Speaking Class

Abstract: This research article described the interactional strategies used by low learners in public qualitative study on whether or not low learners used the aspects of interactional strategies was the main focus. This paper also aimed to know what aspects mostly used and the factors that cause this problem. Observing and interviewing to six subjects regarding on the use of interactional strategies; exemplification, confirmation checks, comprehension checks, repetition, clarification requests, repetition requests, exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Overall, the results of this research concurred with research conducted by Astutik (2017) which stated that students with low speaking ability can speak when they using ISs strategies in speaking activities, especially in English class. Besides, they are also more confidence to speak up because with ISs strategies they have many ways to utter the word in English.…”
Section: )supporting
confidence: 87%
See 1 more Smart Citation
“…Overall, the results of this research concurred with research conducted by Astutik (2017) which stated that students with low speaking ability can speak when they using ISs strategies in speaking activities, especially in English class. Besides, they are also more confidence to speak up because with ISs strategies they have many ways to utter the word in English.…”
Section: )supporting
confidence: 87%
“…This interactional strategy is also a way to overcome students' anxiety in speaking. In her research, Astutik (2017) found that low learners who use more interactional strategies are more confidence in performing their speaking than those who did not.…”
Section: Introductionmentioning
confidence: 98%
“…Language learned by kindergarten students especially those in the region is not only the first language (local language) or the second language (Bahasa Indonesia) but also the foreign language that is English. English has been recognized as an International language; it means that people from cultural, geographical, religious backgrounds have an agreed tool to communicate with each other (Astutik, 2017;Garcia, 2013;Leonardi, 2010;Smith, 2015). The use of English has a significant influence eventhough English is not spoken as often as the local language [Bahasa Indonesia] in everyday life one hears common English phrases; such as I Love You, Thank You, Bye-bye, Hello, Kiss Bye and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Bahadori and Tabatabaei (2016) effectiveness of interactional strategies on speaking accuracy and fluency of EFL learners based on gender. Astutik (2017) showed his concerns about lower learner's interactional strategies in a public speaking class setting. Forbes and Fisher (2018) depicted the impact of students' use of metacognitive learning strategies on confidence and proficiency in foreign language speaking skills.…”
Section: The Application Of Interactional Strategies To English As a Foreign Language Speaking And Listeningmentioning
confidence: 99%